2017
DOI: 10.18632/oncotarget.17928
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous laser ablation for benign thyroid nodules: a meta-analysis

Abstract: PurposeTo evaluate percutaneous laser ablation in treating benign thyroid nodules, we conducted a meta-analysis based on summarizing existing researches.Materials and MethodsA literature search for clinical trial was performed in PubMed, Cochrane Library and Excerpt Medica Database. The qualities of included studies were evaluated. We calculated the indexes with mean difference. Heterogeneity and publication bias were tested and explored. We performed subgroup analyses and sensitivity analysis further.ResultsA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…Thermal ablation is already used in clinical practice for primary and metastatic malignant liver, breast, renal, bone and lung tumors [20][21][22][23] but is not yet regularly used for TNs, despite their validation in Korean and Italian studies [24][25][26][27][28]. Radiofrequency ablation (RFA), and laser ablation have already been studied separately for the treatment of benign TNs [29][30][31][32][33][34] and in many retrospective and some prospective comparative studies with a long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal ablation is already used in clinical practice for primary and metastatic malignant liver, breast, renal, bone and lung tumors [20][21][22][23] but is not yet regularly used for TNs, despite their validation in Korean and Italian studies [24][25][26][27][28]. Radiofrequency ablation (RFA), and laser ablation have already been studied separately for the treatment of benign TNs [29][30][31][32][33][34] and in many retrospective and some prospective comparative studies with a long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, laser ablation possibly reduces the invasiveness of the procedure due to its smaller energy applicators [10,22]. A recent meta-analysis of 19 papers and 2137 patients confirmed laser ablation to be safe and effective in reducing benign thyroid nodules volume, improving thyroid function and esthetic and ameliorating symptoms of compression, especially for hypervascular nodules [23]. For the treatment of benign thyroid nodule, outcomes of laser ablation seem comparable to RFA, as also shown by a propensity score analysis [10,24].…”
Section: Laser Ablationmentioning
confidence: 88%
“…For larger goiters, methimazole discontinuation rate after the procedure depended on the baseline goiter volume [30]. Laser ablation has been compared to 131 I radioiodine therapy for the treatment of hyperfunctioning benign nodules [23,26,28,30]. Despite a similar reduction in nodule volume, normalization of serum TSH was superior in the radioiodine groups, suggesting laser ablation to be indicated only in the risk of radioiodine-induced hypothyroidism or in pregnant women.…”
Section: Laser Ablationmentioning
confidence: 99%
“…A cost analysis in 2014 suggested that there were potential savings for regional healthcare systems that adopted laser ablation in the management of benign thyroid nodules . A recent meta‐analysis concluded that laser ablation was both safe and effective in volume reduction and relieving pressure symptoms in patients with benign thyroid nodules …”
Section: Benign Thyroid Nodulesmentioning
confidence: 99%